FAKTOR-FAKTOR YANG MEMPENGARUHI KAPABILITAS LEMBAGA ADAT MELAYU RIAU DALAM MENDUKUNG PENCAPAIAN VISI PROVINSI RIAU 2020 - Syed Agung Afandi; Muslim Afandi (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
The Riau Malay Customary Institution is a community organization founded by Riau Malay community in response to the decline in the existence of Malay culture in Riau Province. This organization was founded in 1970 and is the only Malay community organization in Riau Province that was made a partner of the Riau Provincial Government in an effort to achieve the vision of Riau 2020 through the Riau Provincial Regulation No.1 of 2012 concerning the Riau Malay Customary Institution. The purpose of this study was to determine the factors that influence the capabilities of Riau Malay Customary Institutions in achieving the vision of Riau 2020. The method used is a qualitative method with a descriptive approach. The technique of collecting data uses interview, observation and documentation techniques. The results of this study indicate that the factors that influence the capabilities of the Riau Malay Customary Institution in supporting the government’s performance in achieving the vision of Riau Province 2020 are the possession of financial and physical resources, all of which are sourced from the Riau Provincial Government. This organization has human resources that have not been able to support organizational performance, the collaboration between the Provincial Government of Riau and the Riau Malay Customary Institution has not been clear which has a clear roadmap, bad reputation received by the organization because of poor performance, and inconsistent organizational attitudes towards achieving the purpose.